THE BOGOR BUS STATION RELOCATION IMPACT ANALYSIS TO THE BOGOR OUTER RING ROAD (BORR) AND PANGERAN SOGIRI STREET PERFORMANCE - Tri Sudibyo; Imam Muthohar (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
As the main bus station in Bogor, West Java, Baranangsiang bus station is currently located in the crowded city centre, near many offices, campuses and department stores. There is a plan of Bogor’s Dinas Perhubungan Komunikasi dan Informasi (Diskominfo) to relocate the bus station to the new location in the Pangeran Sogiri Street in Tanah Baru area, near the newly built toll road, the Bogor Outer Ring Road (BORR).This research is conducted to analyze the traffic performance impact of the relocation plan of the bus station to the BORR network and the Pangeran Sogiri Street. The traffic data is obtained from the field survey in the Baranangsiang bus station and the BORR network. Some other secondary data are obtained from the Dinas Lalu Lintas and Angkutan Jalan (DLLAJ) Bogor city. Based on the obtained data, a micro simulation model is built by using Aimsun traffic micro simulation program. The analysis is conducted in three traffic performance parameters; the traffic density, speed, and vehicles queue length. With respect to the analysis result, the relocation causes a serious traffic problem to the BORR network and the P. Sogiri Street. To minimize the problem caused by the relocation, three scenarios are proposed and thus simulated based on the findings and observed traffic problems. The first proposed scenario is conducted by widening the P. Sogiri Street and providing a 4-4 toll payment gate system to the BORR. This first scenario is able to reduce traffic problem in some sections, but the average network density, speed and queue length are still high by 132%, -54%, and 200% respectively compared to the existing condition. The second scenario is conducted by widening the P. Sogiri Street and providing a 5-3 toll gate system. This second scenario is also able to reduce traffic problem in most sections, but the average network density, speed and queue length are still high by 248%, -70%, and 95% respectively compared to the main bus station before the relocation. The third scenario is conducted by widening the P. Sogiri into 4 lanes, providing a 4-3 toll gate system, and providing a new access from/to P. Sogiri Street to Bogor city direction. The simulation result shows that the third scenario is considered as the best scenario since in this scenario, the density, speed and queue length are relatively similar compared to the existing condition.